Analysis of selected T cell subsets in peripheral blood after exhaustive effort among elite soccer players - Kostrzewa-Nowak, Dorota (Biochem Med (Zagreb), 2018)
INTRODUCTION: Physical exercise induces developing of naïve T lymphocyte subsets into polarised effector ones by immune system. The aim of the study was to examine the influence of exhaustive effort on the selected Th cell subsets and inflammation markers among soccer players. MATERIALS AND METHODS: Fourteen soccer players aged 18 (16-21) years old performed the progressive efficiency test on mechanical treadmill. Th and Tc memory lymphocytes’ subsets and selected cytokine concentrations pre-exercise, post-exercise and in recovery were analysed by flow cytometry. RESULTS: Physical effort induced changes in Th cell percentages. Increase in recovery Treg and Th17 cell subsets’ percentages in comparison to pre-exercise values were observed (10.98 (9.83-14.07) vs. 3.95 (3.15-5.53), P < 0.001 in autumn; 10.58 (7.54-12.67) vs. 4.83 (3.73-6.81), P < 0.010 in spring for Treg and 29.21 (26.34-32.16) vs. 21.64 (18.48-25.76) in autumn; 27.15 (24.60-29.16) vs. 17.43 (15.83-19.77) in spring, both P < 0.010; for Th17, respectively). Increases in Th1 cell percentages post-exercise (31.86 (28.72-33.72) in autumn, 25.60 (21.50-29.19) in spring, both P < 0.010) and in recovery (34.64 (31.21-38.20) in autumn; 26.68 (25.17-28.07) in spring, both P < 0.001) compared to pre-exercise (22.70 (21.21-26.74) for autumn and 15.64 (14.38-19.63) for spring, respectively) were found. Interestingly, no changes in Th2 cell subsets were found. Post-exercise and recovery changes in IL-6, IL-8, TNF-α and IL-10 were also observed. CONCLUSIONS: It seems that the given effort in the progressive test induced an anabolic effect being related not only with cytokine profile but also with CD4(+) T cells’ differentiation and peripheral distribution.